Evaluating the Mexico city policy: How US foreign policy affects fertility outcomes and child health in Ghana - Jones, Kelly M. (International Food Policy Research Institute, 2011)
US development assistance represents a significant source of funding for many population programs in poor countries. The Mexico City policy, known derisively as the global gag rule, restricts activities of foreign nongovernmental organizations (NGOs) that receive such assistance. The intent of the policy is to reduce the use of abortion in developing countries—a policy that is born entirely of US domestic politics and that turns on and off depending on the political party in power. I examine here whether the policy achieves its aim, and how the policy affects reproductive outcomes for women in Ghana.Employing a woman-by-month panel of pregnancies and woman fixed effects, I estimate whether a given woman is less likely to abort a pregnancy during two policy periods versus two nonpolicy periods. I find no evidence that any demographic group reduces the use of abortion as a result of the policy. On the contrary, rural women significantly increase abortions. This effect seems to arise from their increased rate of conception during these times. The policy-induced budget shortfalls reportedly forced NGOs to cut rural outreach services, reducing the availability of contraceptives in rural areas. The lack of contraceptives likely caused the observed 12 percent increase in rural pregnancies, ultimately resulting in about 200,000 additional abortions and between 500,000 and 750,000 additional unintended births. I find that these additional unwanted children have significantly reduced height and weight for age, relative to their siblings.Rather than reducing abortion, this policy increased pregnancy, abortion, and unintended births, resulting in more than a half-million children of significantly reduced nutritional status.